Les relations culturelles et artistiques France-Écosse au XIXe siècle, ou la réception critique de la peinture écossaise en France - Marion AMBLARD (E-REA)
Since the end of the 13th century the connections between France and Scotland have had a deep impact on several aspects of the cultural and artistic life of both nations. French pictorial art has enjoyed a considerable reputation in Scotland since the 18th century and Scottish museums still continue to organise regular exhibitions of French painting. But what is the reputation of Scottish pictorial art in France? With the development of the Scottish school of painting at the turn of the 19th century, who were the Scottish painters known in France? Why were the French connoisseurs, art critics and painters from that period who were sensitive to contemporary Scottish painting? Was the existence of the Scottish school acknowledged in 19th-century France? Here are some of the issues examined in this paper which investigates the critical reception of Scottish painting in France and sheds light on one aspect of the cultural and artistic relations between Scotland and France in the 19th century.